Batteries: 3D Porous Cu–Zn Alloys as Alternative Anode Materials for Li‐Ion Batteries with Superior Low T Performance (Adv. Energy Mater. 1/2018). Issue 1 (5th January 2018) - Varzi, Alberto; Mattarozzi, Luca; Cattarin, Sandro; Guerriero, Paolo; Passerini, Stefano
Abstract : In article number1701706, Alberto Varzi, Stefano Passerini, and co‐workers report a novel class of lithium‐ion battery (LIB) anodes based on Zn‐rich porous Cux Zn1‐x intermetallic compounds. The carbon‐ and binder‐free electrodes produced by cheap and scalable electrodeposition in aqueous media exhibit, in particular, an extraordinary lithium storage capability at low temperature. These findings may pave the way for more efficient, safer, and faster charging of LIB‐powered vehicles in regions with cold climates.